2022
DOI: 10.1038/s41443-022-00589-x
|View full text |Cite
|
Sign up to set email alerts
|

Thematic analysis of the psycho-sexual symptoms in patients with Peyronie’s disease present on online forums

Abstract: Peyronie’s disease (PD) is a fibrotic disorder of the tunica albuginea that may result in penile deformity, pain, a palpable plaque, and erectile dysfunction. In order to understand the psycho-sexual impacts of PD on patients and their partners, we selected three online forums containing the largest number of threads on PD. Threads focusing on the psycho-sexual impacts posted from January 1, 2011 to January 1, 2021 were compiled, and thematic analysis was performed on Dedoose. There were 277 unique posters, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…PD is a sexual dysfunction recognized for the great impact on men and couples’ mental health. 24 According to a literature review of 2016 by Terrier and Nelson, 25 almost half of the men affected by PD suffer from depressive mood, and described themselves as “abnormal”, “ugly”, “disgusting”, “like a cripple”, and a “half man”. Moreover, previous authors demonstrated that the perception of greater penile curvature degrees increases the psychological consequences of PD, with an overall higher symptomatic burden as scored with the PDQ.…”
Section: Discussionmentioning
confidence: 99%
“…PD is a sexual dysfunction recognized for the great impact on men and couples’ mental health. 24 According to a literature review of 2016 by Terrier and Nelson, 25 almost half of the men affected by PD suffer from depressive mood, and described themselves as “abnormal”, “ugly”, “disgusting”, “like a cripple”, and a “half man”. Moreover, previous authors demonstrated that the perception of greater penile curvature degrees increases the psychological consequences of PD, with an overall higher symptomatic burden as scored with the PDQ.…”
Section: Discussionmentioning
confidence: 99%
“…Once diagnosed, PD is very difficult to treat and its psychological and physical effects on patients’ quality of life is severe ( 12 ). Studies have identified psychological distress, depression, anxiety, sexual dissatisfaction, and disruptions in relationships associated with PD ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%